Asymmetric Hydrogenation of tert‐Alkyl Ketones: DMSO Effect in Unification of Stereoisomeric Ruthenium Complexes1. Issue 35 (10th July 2013) - Yamamura, Tomoya; Nakatsuka, Hiroshi; Tanaka, Shinji; Kitamura, Masato
<x xml:space="preserve">Abstract</x> Face off: The ruthenium complexes of a new axially chiral PNN ligand (L) are highly efficient in the presence of dimethylsulfoxide (DMSO) for hydrogenation of both functionalized and unfunctionalized tert‐alkyl ketones. DMSO is thought to narrow down the many possible complex stereoisomers into a single facial L/Ru complex, thus enhancing the reactivity, selectivity, and productivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>